Care Plans for Native and Prosthetic Joint Septic Arthritis, and Acute Hematogenous and Chronic Osteomyelitis - Stephen D Shafran; The Septic Arthritis∕Osteomyelitis Outpatient Intravenous Antibiotic Therapy Working Group (Canadian Journal of Infectious Diseases)
The current paper presents care plans for the treatment of septic arthritis of native and prosthetic joints, as well as for acute hematogenous and chronic osteomyelitis. A nursing care plan for septic arthritis and osteomyelitis is included, along with pathogen-specific therapy for common pathogens, including Gram-positive and Gram-negative cocci.